PENGEMBANGAN MODEL PEMBELAJARAN NOMOR ACAK UNTUK MENINGKATKAN EFEKTIVITAS BELAJAR MAHASISWA PGSD FKIP UNIVERSITAS RIAU - Zufriady, Zufriady (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2018)
The development of Nomor acak learning model is motivated by the desire to improve teaching and learning processwith the aim to improve the effectiveness of teaching and learning. This model approach emphasizes the readinessof students in the learning process. Theoretically this development model is based on two theories of constructivismand low of readiness developed by Thorndike. This research uses the Research and Development method which isreferenced from the theory of bord and gall. At this time the stages used are four stages: first phase of literaturestudy, second stage designing model, third stage of application & feasibility test, fourth stage of compilation andpublication. Based on the results of research and development of instruments that have been developed about thedevelopment of learning models have been effectively used. This can be seen from the acquisition of thequestionnaire distributed above the category that has been determined with the percentage of classical 79.83%. andfrom the results of the FGD conducted there are several inputs and improvements that have been improved.